The Effectiveness of a Group Program Based on the ‎Theory of Cognitive Behavioral Therapy in Improving Self-differentiation and Reducing ‎Hierarchical Ambiguity among Women Working in ‎the Medical Field - Al-Qarralah, Abdulnaser (Jordan Journal of Educational Sciences, 2022)
This study aimed at investigating the effectiveness of a group program based on the theory of family cognitive behavioral therapy in improving self-differentiation and reducing hierarchical ambiguity among women working in the medical field. In order to achieve the study objectives, the researcher selected a sample of females working in the medical fiele in Amman with a total of (18) women who were divided into two groups ;the experimental group (n=9) and the control group (n=9). Two scales were developed; one for self-differentiation and the other for hierarchical ambiguity, in addition to a psychological intervention program based on cognitive behavioral therapy. After applying the program on the individuals of the experimental group, the results showed that the experimental group improved in self-differentiation and witnessed a statistically significant decline in hierarchical ambiguity in comparison with the control group. Improvement continued among the individuals of the experimental group after one month of follow-up. Based on the results, the study recommended the necessity of taking care of women in the mid-life period as well as designing guidance programs for them, particularly those working in the medical field